2021
DOI: 10.3389/fmars.2021.681563
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Response to Stony Coral Tissue Loss Disease Transmission in M. cavernosa and O. faveolata From Florida

Abstract: Since 2014, corals within Florida’s Coral Reef have been dying at an unprecedented rate due to stony coral tissue loss disease (SCTLD). Here we describe the transcriptomic outcomes of three different SCTLD transmission experiments performed at the Smithsonian Marine Station and Mote Marine Laboratory between 2019 and 2020 on the corals Orbicella faveolata and Montastraea cavernosa. Overall, diseased O. faveolata had 2194 differentially expressed genes (DEGs) compared with healthy colonies, whereas diseased M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 80 publications
5
42
0
Order By: Relevance
“…Previous studies on coral disease and immunity have successfully identified genes induced by disease that contribute to biological processes such as apoptosis, autophagy, extracellular matrix maintenance, lipid metabolism, and protein trafficking (18)(19)(20)(21)(22). However, comparing immune responses between coral species that differ in disease resistance or susceptibility, linking specific disease phenotypes to gene expression, and determining adaptive or plastic disease resistance-associated expression patterns are understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on coral disease and immunity have successfully identified genes induced by disease that contribute to biological processes such as apoptosis, autophagy, extracellular matrix maintenance, lipid metabolism, and protein trafficking (18)(19)(20)(21)(22). However, comparing immune responses between coral species that differ in disease resistance or susceptibility, linking specific disease phenotypes to gene expression, and determining adaptive or plastic disease resistance-associated expression patterns are understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Although functional genomic evidence for pleiotropy is currently lacking for corals, bleaching resistance in adults can come at the cost of other fitness-related traits (Cornwell et al, 2021; Shore-Maggio et al, 2018), suggesting pleiotropy can constrain thermal adaptation within life stages. Putatively pleiotropic genes identified in the present study include tumor necrosis factor receptor superfamily 19 and a peroxidasin homolog, which have been previously implicated as key players in both the immune (Traylor-Knowles et al, 2021) and environmental stress response (Barshis et al, 2013b; Louis et al, 2017) in coral, yet their role in developmental modulation is unknown. The present study provides the first evidence for developmental pleiotropy in corals at a molecular level and emphasizes the need for functional and quantitative genetics to be conducted across multiple life stages to determine the costs and limits of thermal adaptation.…”
Section: Discussionmentioning
confidence: 91%
“…Peroxinectins are best characterised in arthropods where they mediate the immune response via cell adhesion (Johansson et al 1995) and prostaglandin synthesis (Park et al 2014). Heat stress experiments in molluscs (Lang et al 2009), and corals (Voolstra et al 2009; Shinzato et al 2021; Traylor-Knowles et al 2021) consistently identify peroxinectin-like proteins as differentially expressed, and there is evidence that they have undergone recent expansion in some heat-tolerant coral lineages (Shinzato et al 2021). Unfortunately the role of peroxinectins in corals has been obscured because many peroxinectin-like proteins are annotated as peroxidasin homologues in the NCBI nr database.…”
Section: Discussionmentioning
confidence: 99%